Testing the Long-Term Profitability of the Short-Term Reversal Strategy - Tsiu, Matsepe Modikeng Theodore (Department of Finance and Tax, 2020)
The purpose of this investigation was to test the theoretical possibility of an investor earning a positive cash return from the activities of the stock market despite effectively holding no position at all in said market. The sample data were the daily returns for the shares of the 780 companies listed on the NASDAQ and the New York Stock Exchange (“NYSE”), which fell within the top 500 listed companies by market capitalisation between 1 January 2005 and 31 December 2017. The reversal strategy’s performance was evaluated using portfolios constructed as quantiles of 100 or 500 shares, respectively, where the investor had the option of implementing the reversal strategy immediately after an information-gathering period closed or a day thereafter. The time intervals used were 1 January 2005 to 29 September 2008 (the day the Dow Jones Industrial Average crashed by 777.68 points), 29 September 2008 to 31 December 2017 and 1 January 2005 to 31 December 2017. Of the 1000 portfolios tested in each time interval, at least 416 had positive average returns in every time interval. Of the portfolios that had positive average returns over the time intervals, at least 66 had statistically significant average returns in every time interval. The best-performing portfolio for the entire sample period was a combination of the best-performing pre-crash and post-crash portfolios - an investor who held that portfolio realised a cumulative return of approximately $61.39 for every $1 invested. The conclusion was that it was theoretically possible for an investor to earn a positive cash return from the market’s activities despite effectively holding no position at all in the market. Consequently, it was concluded that the strong form of Fama’s (1970) Efficient Market Hypothesis was disproved. Future research should include out-of-sample tests, tests that include restrictions on short selling and tests that consider the impact of trading costs on portfolio performance, to render the conclusions of this investigation more practically applicable to investors.